The Potential of Building Tourist Cities by Using Existing Resources in Uzbekistan with an Innovative Approach - Madina M. Khashimova; Shakhzod F. Turakulov (Universitas Muhammadiyah Sidoarjo, 2020)
This article reflects the construction of tourist cities using the resources available on the territory of Uzbekistan. The benefits of utilisation for the development of tourism infrastructure from geological cities that are not exploited, included in the available resources, have been analyzed. The high level of efficiency in the use of geological cities is based on the availability of economic infrastructure, which is recognized as the application of this infrastructure in the construction of tourist cities is low in costs. The article shows the specific natural anchors of three ecotouristic objects, the srategic plans for effective use of these anchors. Proposals on the expediency of the establishment of camps, bags, summer recreation zones are included in these facilities. The abundance of excursion facilities and attractions in the objects of ecotourism expressed their views on the possibility of opening remarkable travel destinations. And the steep slopes of the mountain are shown to be a special training area for training highly qualified climbers. Reflecting the peculiarities of the nature of the objects of the ecosystem, the role of these settlements with unique natural conditions in the development of tourism is established. The potential for the construction of such ecotouristic cities in the Republic of Uzbekistan is high, and the growth in the efficiency of the use of such potentials is reported to increase the number of tourists coming from foreign countries to Uzbekistan.